Tax systems and tax reforms in Europe - Bernardi, Luigi (Luigi); Profeta, Paola, 1959- (London ; New York : Routledge, 2004)
This comprehensive volume provides impressive analyses of tax systems and tax reforms in various European countries including France, Germany, Italy and the United Kingdom. With a preface from Vito Tanzi and a large range of contributions, the book identifies and analyzes the main common forces that drive fiscal reforms such as globalization, European reunification and fiscal federalism.
Includes bibliographical references and index.
nmn 04/05/13
Loans
Keywords: Taxation -- European Union countries